Changes in Men’s Salivary Testosterone and Cortisol Levels, and in Sexual Desire after Smelling Female Axillary and Vulvar Scents - Mondragón-Ceballos, Ricardo; Hernández-López, Leonor; Cerda-Molina, Ana L.; de la O Rodriguez, Claudio E.; Chavira-Ramírez, Roberto (Frontiers in Endocrinology, 2013)
Several studies have shown that a woman’s vaginal or axillary odors convey information on her attractivity. Yet, whether such scents induce psychoneuroendocrinological changes in perceivers is still controversial. We studied if smelling axillary and vulvar odors collected in the periovulatory and late luteal phases of young women modify salivary testosterone and cortisol levels, as well as sexual desire in men. Forty-five women and 115 men, all of them college students and unacquainted with each other, participated in the study. Female odors were collected on pads affixed to the axilla and on panty protectors both worn the entire night before experiments. Men provided five saliva samples, a basal one before the smelling procedure, and four more 15, 30, 60 and 75 min after exposure to odors. Immediately after smelling the odor source, men answered a questionnaire rating hedonic qualities of scents, and after providing the last saliva sample they answered questionnaire on sexual desire. We found that periovulatory axillary and vulvar odors increased testosterone and cortisol levels, with vulvar scents producing a more prolonged effect. Luteal axilla odors decreased testosterone and cortisol levels, while luteal vulva odors increased cortisol. Periovulatory axilla and vulva scents accounted for a general increase of interest in sex. These odors were also rated as more pleasant and familiar, while luteal vulvar odors were perceived as intense and unpleasant.